(Invited) Dipoles in Gate-Stack/FDSOI Structure. (16th August 2017) - Reimbold, Gilles; Leroux, Charles; Suarez Segovia, Carlos; Mohamad, Blend; Kumar, Pushpendra; Garros, Xavier; Domengie, Florian; Blaise, Philippe; Ghibaudo, Gerard
Abstract : This paper addresses the measurement and the understanding of several dipoles which may be present in the FDSOI gate stack (generation 28-14-10 nm). These dipoles are namely the intrinsic SiO2 /high-k dipole, the dipoles induced by Lanthanum and Aluminum doping to change the effective workfunction, and the Germanium induced dipole in the case of SiGe channel. Some reliability studies (NBTI) will be presented on these stacks, leading to an interesting regard on physical mechanisms.